Results of Observational Study and Integration of Epinastine 0,05% in Treatment Algorythms of Patients with Seasonal Allergic Conjunctivitis - D. Yu. Maychuk; E. A. Drozdova; A. A. Tarkhanova; E. E. Zinych (Oftalʹmologiâ)
Objective. To assess tolerability and the time of onset of clinical effect of dual-action antihistamine agents — Epinepta® (epinastine 0.05 %) and olopatadine 0.1 % in patients with seasonal allergic conjunctivitis (SAC).Subjects and methods. This was a prospective multicenter observational study. One hundred fifty patients with SAC (n = 150) were included into the study and divided into two groups (n = 75) in each. Patients in group 1 received epinastine 0.05 %, while patients into group 2 received olopatadine 0.1 %. Evaluation of clinical symptoms severity was performed using itching scale, hyperemia Efrone scale, eyelid swelling scale, lacrimation P. Munk scale, Shirmer test and Norn probe. Patients and healthcare providers satisfaction rate was assessed by Likert scale, patients self-control diary that helped to assess dry eye severity symptoms. Treatment period lasted 14 days.Results. Seasonal allergic conjunctivitis treatment with epinastine 0.05 % or olopatadine 0.1 % was equally effective. However epinastine 0.05 % was causing dry eye symptoms in lesser degree than olopatadine 0.1 %. These results refer to all parameters assessed by patients’ self-control diary — itching, discomfort, burning, eye blockage feeling.Conclusion. The study evaluated epinastine 0.05 % advantages compared to olopatadine 0.1 % in tear film preservation and causing less pronounced symptoms of dry eye in patients with acute seasonal allergic conjunctivitis. Monotherapy of seasonal allergic conjunctivitis with epinastine 0.05 % demonstrated high efficacy and lead to SAC clinical manifestations regress. Epinastine 0.05 % is recommended as a first line treatment of SAC.